English: Bahasa Indonesia - Achmad Faisal (CV. AFDIFAL MAJU BERKAH, 2025)
Jati Visions Raya has used information technology in its company, namely System Application and Product in Data Processing (SAP) to facilitate its business operations, one example is recording inventory, but there is an imbalance between the amount of inventory in SAP and in the warehouse. the researcher was encouraged to conduct research which aims to find out analyze, examine more deeply the results of implementing and evaluating SAP in Inventory Logistics and its implications for Companies Performance CV. Jati Visions Raya. This research method uses a qualitative approach with the data used primary and secondary. Primary data obtained through in-depth interviews with informants who served as Logistics Managers, Warehouse Admins, and Finance Managers is a data collection method. In addition, secondary data was obtained from inventory data from January 2024. Fishbone diagrams were used in this investigation to help find potential solutions to the problem and identify the main cause of the problem. The fishbone diagram explained that there are many factors that are the source of the difference in inventory in the warehouse and the SAP system. The investigation resulted in four causal factors: methods or processes, human intervention, raw materials, and machinery or technology. Employee performance always occurs after using SAP, the company's performance improvement becomes very significant, especially in inventory and logistics in seeing the real stock in the field and receiving goods there is a quality control process.